Isolation and identification of Mycobacterium tuberculosis from patients that have relipase infection at Nasseriya province during 2004-2009 year - Hassan Awda’a, Qasim (University of Thi-Qar Journal of Science, 2019)
Mycobacterium tuberculosis that cause diease for inhaled and reach lungs , the disease results from proliferation at organisms and interactions with the host, 3 months or years injected BCG in the normal host, and there the production and development of lesions are caused by healing and multiplication at the lung or progression are determined chiefly by the number of mycobacteria in the inoculum and their subsequent, and the Mycobacterium inter the host, tuberculosis is caused by Mycobacterium tuberculosis ,persons who have tuberculosis in their lungs can release tiny moulculos contain Mycobacterium tuberculosis into the air by coughing , ,in 2004 a total of 200 patients (108 male and 92 femal),in 2005 a total of 67 patients (57 male and 10 femal), in 2006 a total of 38 patients (29 male and 9 femal ) , in 2007 a total of 28 patients (19 male 9 female ),in 2008 a total of 2 patients ( 2 male and non in female ),in 2009 a total of 67 patients (53 male and 14 femal) , the males patints a total of 268 and females patints a total of 134 the total from 2004 to 2009 total of 402 patients , the aim of study isolation and identification of Mycobacterium tuberculosis from patients that have relipase infection at Nasseriya province during 2004-2009 year